Late XIX - Early XX Centuries Traditional Forms of Agricultural Technology - Fakhriddin Rahmonov (Researchparks Publishing, 2022)
This article scientifically reveals the forms of traditional agriculture of the population of Southern Uzbekistan in the late XIX - early XX centuries on the basis of available sources and literature, as well as field data.